Three-year trends in dietary behaviours among mothers, teenagers and children from SNAP-Ed (Supplemental Nutrition Assistance Program–Education) eligible households across California - Molitor, Fred (Public Health Nutr, 2020)
OBJECTIVE: To examine trends from 2015 to 2017 in dietary behaviours and diet quality among low-income mothers, teenagers and children. DESIGN: Cross-sectional telephone surveys using a validated 24 h dietary assessment. SETTING: Randomly sampled households with incomes ≤185 % of the US federal poverty level across California. PARTICIPANTS: Survey participants were 13 247 mothers (≥18 years), 3293 teenagers (12–17 years) and 6043 children (5–11 years). Respondents were mostly Latino. RESULTS: Over the 3-year study period, consumption of fruits and vegetables with and without 100 % fruit juice increased (P ≤ 0·05) by at least 0·3 cups/d for mothers, teenagers and children. Intake of water also increased (P ≤ 0·001) by more than 1 cup/d for mothers and children and 2 cups/d for teenagers. Sugar-sweetened beverage (SSB) consumption was unchanged over the 3 years. Overall diet quality, as assessed by the Healthy Eating Index-2015, improved (P ≤ 0·01) for mothers, teenagers and children. Covariates for the fifteen regression models (three age groups by five outcome variables) included race/ethnicity, age, education for mothers, and gender for teenagers and children. CONCLUSIONS: The observed increases in fruit and vegetable intake and improvements in overall diet quality during the 3-year period suggest that low-income Californians may have lowered their risk of preventable diseases. However, more intense or strategic SSB-reduction interventions are required. Regional- or state-level, population-based surveillance of dietary behaviours is useful for public health nutrition policy and programme decision making, and can be used to assess potential trends in future negative health outcomes and related costs associated with poor dietary behaviours within at-risk populations.